A "Shortage of Women": Gender and Medical Care in the Highlands of Irian Jaya, Indonesia - Butt, Leslie (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
This paper describes two distinct features ofthe Irian Jaya highlands: local practices that may contribute to gender imbalances of up to 250 menfor every 100 women; and regional health care policy and practice. Ideally, medical care and local needs complement one another, but the demographics of the region belie primary health care mandates to improve the well-being of all. Healing programmes appear more responsive to Indonesian development agendas than to community needs. This paper suggests that missionaries and medical staff do intervene, notably in events surrounding childbirth, but tend not to address the issue of long-term discrimination against women. The flexible nature of the concept "health" within primary health care allows women to fall into the void between policy and local practice.